Tools and Strategies for Managing Penans’ Indigenous Botanical Knowledge - Narayanan, A/L N. Kulathuramaiyer; Tariq, Zaman; Yeo, Alvin Wee; Salfa, Kamazura; Faheem, Ullah (2012)
The formalised storage of Indigenous Knowledge (IK) is gaining increasing currency across the globe. There are many initiatives of using ICT tools for documenting IK implemented by various organisations around the world. However, technology and databases alone do not provide adequate management system for IK. In this paper, we will briefly present the approach used in eTORO project by the Institute of Social Informatics and Technological Innovations, Universiti Malaysia Sarawak with active participation of the local community in Long Lamai, Sarawak. The main objective of the eTORO project is to facilitate the community in preserving and transferring their indigenous botanical knowledge through proper documentation processes.